Genetic polymorphism in HSP90AA1 gene and associated with the heat tolerance coefficient in Holstein cows at south of Iraq - AL-Luhaibe, Khalid Adnan Abdullah Aitha; Al-Azzawi, Salih Hassan Jassim (Journal of agricultural, environmental and veterinary sciences, 2019)
This study was carried out in Iraq at the Taj Al-Nahrain Animal Production located in Diwaniyah province, one of the governorates of the Euphrates Middle, located south of the Iraqi capital Baghdad, about 180 kilometers away. the study was undertaken to investigate the association of single nucleotide polymorphisms(SNPs) of HSP90AA1 gene with some of reproductive and productive traits and all so heat tolerance coefficient during different season(warm, moderate, cold) Here are the most important results obtained during this study. The analysis revealed a site of heterogeneity in the HSP90AA1 gene within the Exon3 region at site 1690.The genotype of the heterogeneity site was recorded with two genotypes: TT(Wild) and genotype TC ) Heterozygous), and the heterogeneity of the nitrogen bases was determined. The results showed that the nitrogenous base of T was changed and replaced with the nitrogenous base C Within the heterogeneity site, the results show a significant difference at the level(P0
Keywords: heat shock gene; HSP90AA1; heat tolerance coefficient